Prevalence, barriers and factors associated with parental disclosure of their HIV positive status to children: a cross-sectional study in an urban clinic in Kampala, Uganda - Osingada, Charles P.; Okuga, Monica; Nabirye, Rose C.; Sewankambo, Nelson K.; Nakanjako, Damalie (BMC Public Health, 2016)
Background: Disclosure of parental HIV status is associated with a number of positive outcomes such as improved adherence to clinic appointments, lower levels of parental anxiety and depression, and mutual emotional support between parents and their children. Very few studies in low-resource settings have addressed the issues of parental disclosure of their HIV status to their children. Methods: A cross-sectional study was conducted among adult parents attending HIV/AIDS prevention, care and treatment clinic at Makerere University Infectious Diseases Institute (IDI), Kampala, Uganda. Participants were interviewed using the Parent Disclosure Interview (PDI) questionnaire which is a standard tool developed specifically for HIV infected parents. Data were analyzed using STATA version 13.1. Results: Of 344 participants, only 37 % had told at least one of their children that they were HIV positive. Barriers to disclosure were fear that children may tell other people about the parent’s HIV status, desire not to worry or upset children and perceptions that children may not understand. Age of the parent, religion and having someone committed to care of the children were positively associated with parental disclosure of their HIV positives status. Attainment of tertiary level of education was negatively associated with parental disclosure of their HIV status. Conclusions: Parental disclosure of a positive HIVstatus to their children is still low in urban Kampala. There is therefore need to develop locally relevant interventions so as to increase rates of parental disclosure of a positive HIV status to their children and thus promote open and honest discussions about HIV/AIDS at family level
Keywords: HIV Disclosure; Prevalence; Barriers; Associated factors; Uganda